Polypharmacy-associated potential contraindications of drug prescriptions in patients with primary angle closure disease in a real-world setting - Fumiaki Tanaka; Naoki Shibatani; Kazumi Fujita; Hiroaki Ikesue; Satoru Yoshimizu; Nobuyuki Muroi; Yasuo Kurimoto; Tohru Hashida (BMC, 2021)
Abstract Background Primary angle closure disease (PACD) is a type of glaucoma in which the intraocular pressure (IOP) is increased because of the blockage of the anterior chamber angle. Medications contraindicated for patients with PACD, such as anticholinergics, cause mydriasis, and can elevate IOP. However, anticholinergics are currently contraindicated only for primary angle closure glaucoma (PACG) in Japanese package inserts. In this study, we investigated the prescription status of medications contraindicated for PACD, such as anticholinergics, in patients with PACD scheduled for eye surgeries. Methods Forty-three Japanese patients diagnosed with PACD at Kobe City Eye Hospital, Japan, and scheduled hospitalization for eye surgeries between December 2017 and July 2018, were included. Data, including sex, age, diagnosis, IOP, anterior chamber depth, and patients' regular medications prior to hospitalization, were collected for each patient from the electronic medical records. Results The number of patients with chronic primary angle closure (CPAC) and acute primary angle closure (APAC) was 35 (81.4%) and 8 (18.6%), respectively. Among all the 43 patients with PACD, 8 (18.6%) received 15 medications that are potentially contraindicated for PACD by non-ophthalmologist. According to medication categories, benzodiazepine hypnotics were the most commonly prescribed. Among the 8 patients with APAC, 2 (25.0%) had routinely received medications contraindicated for PACD. The median number of all kinds of prescriptions on the day of hospitalization was significantly higher for patients who received medications contraindicated for PACD than for those who did not receive them (p = 0.010). Conclusions About 20% of patients with PACD received medications potentially contraindicated for PACD, such as anticholinergics. Attention should be paid to patients prescribed multiple drugs for adverse events, such as increase in intraocular pressure.